Study of Soil Contamination with Radioactive Radon Gas in Industrial Environments - Al- Sultani , Karrar Hayder; Al-Shammari , Ali Hammood Rhaif; Aziz , Zainab Nadhum (American Journal of Biology and Natural Sciences, 2025)
Aims of research to measure the concentrations of radioactive radon gas in brick production factories in area of Shomali- Babylon, 13 soil samples were selected and collected from inside the work sites, the CR-39 nuclear trace detector It has been approved for measurement and analysis, lowest of concentration was 604.55 ± 7.11 Bq/m³, while highest of concentration was 1663.64 ± 15.89 Bq/m³. The overall average of the study samples was 1300.35 Bq/m³, Exceeded the safe level of 600 Bq/m³. These results are considered indicators of health impact to workers and the local population, necessitating adherence to occupational safety standards by workers and the need to conduct ongoing biological and environmental studies.